Model-driven engineering of information systems principles, techniques and practice - Cretu, Liviu Gabriel; Dumitriu, Florin (Apple Academic Press, 2015)
Model-driven engineering (MDE) is the automatic production of software from simplified models of structure and functionality. It mainly involves the automation of the routine and technologically complex programming tasks, thus allowing developers to focus on the true value-adding functionality that the system needs to deliver. This book serves an overview of some of the core topics in MDE.